Computer Game Addiction and Loneliness in Children - Hülya KÖK EREN; Özlem ÖRSAL (Tehran University of Medical Sciences, 2018)
Background: We aimed to determine the level of computer game addiction and loneliness among 9-10-yr-old children. Methods: The study was conducted with 4th-grade students at a primary school, located at the city center, during 2017-2018 academic years. There was no sampling in the research, all 4th-grade students of the school were reached. "Personal Information Form", "Computer Game Addiction Scale" and "UCLA Loneliness Scale" were used for collecting data. Mann Whitney U test, Kruskal Wallis test, and Correlation Analysis were used to evaluate the data of the research. Results: 50.7% (n=104) of the students were female, most frequent number of sister/brother was one 39.0% (n=80), both their mother 31.7% (n=65) and their father 34.1% (n=69) were mostly high school graduated. The average scores that students got from the scales were; 48.66±.27.02 (min.: 21.00, max.: 105) for "Computer Game Addiction Scale" and 40.55±8.50 (min: 22.00, max.: 64) for "UCLA Loneliness Scale". A weak, positive and significant relationship was found between students' loneliness scale scores and computer game addiction scale scores (r=0.357; P<0.000). Conclusion: A significant relationship was found between students' computer game addiction and loneliness. It is suggested to perform children's loneliness and computer game addiction assessments, evaluate effectiveness and establish a rehabilitating treatment system among school-hospital-family for abnormal cases.